A chain mediation model reveals the association between metacognition and quality of life in hematologic tumor patients - Chunyan Cheng; Meiqiong Zheng; Fan Yan; Yanrong Wu; Ting Li; Zhengfang Cao; Jiaojiao Yue; Pan Chen; Zhongxia Zheng; Tongfang Fan; Chunpeng Li; Panpan Cui (Scientific Reports, 2024)
Abstract The study aims to explore the relationship among metacognition (MC), fear of disease of progression (FoP), psychological distress (PD), and quality of life (QoL), and verify whether FoP and PD have a chain mediating effect between MC and QoL. 231 hematologic tumor patients in a large tertiary hospital were investigated by using Meta-Cognitions Questionnaire-30, Fear of Progression Questionnaire-Short Form, Hospital Anxiety and Depression Scale, and Functional Assessment of Cancer Therapy scale. Data analyses were performed using IBM SPSS (version 25.0) and the PROCESS macro (version 4.1). The results showed that the direct impact of MC on QoL was not statistically significant. However, the indirect influence of MC on QoL manifest through the independent influences of PD and FoP, as well as the chain mediating effect of “PD → FoP.” In addition, all four dimensions of QoL (physical, social and family, emotional, and functional) satisfy the chain mediation model, except for the social and family domain. These insights advance our comprehension of the intricate interplay between MC and QoL, underscoring the importance of improving MC to alleviate patients' PD, mitigate FoP, and ultimately improve the QoL of hematologic tumor patients.